Petroleum Hydrocarbon Distribution Features in Water and Sediment off Fujian Shore - 王宪 徐鲁荣 李文权 李凌云 钱爱红 (Chinese journal of oceanology and limnology, 2003)
This study on the distribution features of petroleum hydrocarbon in water and sedi-ment off the Fujian shore using data obtained from the baseline research on oceanic contamination in Fujian showed that:during the research preiod,petroleum hydrocarbon concentrations in water varied from 5.77μg/L to 37.28μg/L,averaged 14.48 μg/L;was lower in the wet seasson than in the dry season;and was highest in the Minjiang Estuary and Jiulong Estuary in both seasons ,The petorleum hydrocarbon concentrations in shore sediment varied from 14.48 mg/kg to 784.36 mg/kg,averaged 133.3 mg/kg ,and was closely related to sediment types (granularity).